Water treatment analysis guide - Morrison, Wilke (Department of Civil Engineering, 2020)
The treatment of water up to potable/drinkable standards is a complex process, with many variables and parameters impacting on each other. In South Africa drinking water delivered to consumers must meet the requirements as recorded in the South African National Standards (SANS). Today, more so than ever, there are a number water sources that can be exploited and treated to provide safe drinking water, namely; surface water (dams and rivers), sea water, ground water and treated wastewater. The focus of this dissertation is on surface water; however, reference is made in the first sections with regards to sea water and ground water. The first step in designing a treatment process begins with analysis of the raw water source. Unfortunately, there is not a one size fits all approach and it is left up to the process engineer to find the correct method of investigation. This can be a daunting task, especially if lacking in experience and available information. The first part of this dissertation focusses on just that. It prescribes the method of sampling and aims to provide the reader with context on when to and what to test for. It goes further to suggest how the results may influence the process design and how certain contaminants can be removed. It also draws the attention to the sampling timeframe required, to obtain representative information, encompassing fluctuations in water quality. The second part of this dissertation describe the methods for designing a conventional water treatment system, comprising; aeration, coagulation, flocculation, dissolved air floatation, sedimentation, filtration and disinfection. It also comments on the water quality that warrants certain process steps to assist the process engineer in choosing the correct configuration. For most steps the design approach of two or more technologies are presented. This allows the process engineer to consider which technology best suits the application at hand. The design procedures are programmed into an, excel based, software model, which permits quick and easy design. A brief description of how the software model can be used is also covered. The results given by the software model is validated through a set of examples, appended to this document. Ultimately it is concluded that although this dissertation provides a guide for designing a treatment process it is not an encompassing tool that considers all the intricacies involved. That is, there are too many factors involved and considerations required, and cannot all be captured in one dissertation such as this. As such, it is finally recommended that any design attempts should be conducted by a suitably qualified and experienced process engineer that may use this dissertation to augment their design development.